Overconfident executives can be beneficial for shareholders in a particular context? - Cengiz, Umur (2020)
Past research shows that a heuristic bias push executives to make more mergers and acquisitions, even when these mergers are clearly value-destroying for their shareholders. But usually, they are, overconfident people, the one promoted to CEO by the board. This study examines the role of overconfidence in a merger fails and tries to show that in a particular context such that overconfident managers actually can be beneficial. Using a sample of mergers with applied criteria, I found that the board of directors can prevent excessive cash use in merger financing. Overconfidence indeed helps them explain the numbers of mergers completed, but not specifically the conglomerate mergers completed. I test the hypothesis with the market reaction at the merger announcement with the event study method and found that, contrary to the literature, overconfident CEOs can be beneficial for shareholders, with making less value-destroying mergers and acquisitions. As far as I know, this is the first empirical research that describes overconfident executives as manageable and beneficial. Hence, they are favourable for shareholders compare to their rational peers. My findings also support there is no “learning curve” in CEOs, independent from their exposition to heuristic bias. It is rather difficult to investigate merger learning since they are unique and not comparable easily. But when we look at the “market reaction” perspective, it is clear that executives do not make better decisions by time in other words, they do not learn with time.